"Divorce burnout" among recently divorced individuals. (1st April 2020) - Hald, Gert Martin; Ciprić, Ana; Strizzi, Jenna Marie; Sander, Søren
Abstract: Traditionally, the concept of burnout has been applied to the workspace but recent research suggests its applicability to more general contexts such as the family sphere. The present study applies burnout to the divorce context and (a) proposes and statistically tests the Divorce Burnout Model (DBM), (b) investigates the contribution of sociodemographic variables and divorce characteristics to burnout scores, and (c) investigates the relationship between burnout scores and the number of sick days and days of absence from work. Using a cross‐sectional design and a sample of 1, 856 recently divorced Danish citizens, multigroup confirmatory factor analysis verified the DBM´s good fit to data. Using this model, for men, it was found that fewer previous divorces, former spouse initiation of divorce, not having a new partner and a higher degree of conflict significantly predicted higher levels of divorce burnout. For women, lower income, former spouse divorce initiation, not having a new partner, and a higher level of conflict significantly predicted higher levels of divorce burnout. Across gender, burnout scores were found to significantly predict number of sick days and days of absence from work in the past 3 months over and above sociodemographic variables, divorce related characteristics, and depressive symptoms.